Metropolitan DWDM a dynamically configurable ring for the KomNetfield trial in Berlin. - Stoll, D. (IEEE Communications magazine)
We present the system concept of a dynamically configurable all-optical add/drop multiplexer for metropolitan wavelength division multiplex rings using dense channel spacing (DWDM). We first outline the essential network requirements. Subsequently, an optical system concept is presented that meets these requirements. In the network elements, innovative all-optical switching technology is employed. Tunable fiber Bragg gratings that perform routing functions by wavelength filtering are discussed in more detail. The system is laboratory-tested. It has been installed in Berlin for a multi-vendor field trial within the German research program ?KomNet.? Three optical add/drop multiplexers form a dynamically configurable Metro DWDM ring. Metro DWDM accommodates high bandwidths: a metropolitan ring that provides 0.8 terabit/s ring capacity has been demonstrated. Furthermore, Metro DWDM can provide optically transparent channels enabling the transport of various data formats simultaneously, e.g., SONET/SDH and Gigabit Ethernet. Conversion to a standard format becomes obsolete. The all-optical add/drop multiplexer (OADM) presented provides both manual and dynamic configuration. The system concept of the OADM is developed starting with basic metropolitan DWDM network requirements. The features of the DWDM ring are described, followed by a presentation of the system concept of the flexible OADM. Our focus is on dynamic configuration techniques. Since tunable fiber Bragg gratings are promising components for dynamic optical channel switching, this technology is treated in more detail